Return Migration and Economic Development of the Home Country: A Comparative Study between Kazakhstan and South Korea - Ж.С. Исаева; Су Ын Ки (Halyk̦aralyk̦ k̦atynastar ža̋ne halyk̦aralyk̦ k̦u̇k̦yk̦ seriâsì)
This paper explores the impact of return migration on economic development in Kazakhstan and South Korea. The primary focus is on examining the involvement of return migrants in the labor market, entrepreneurship, and socio-economic adaptation. The research is theoretical in nature, founded on a comparative study alongside an analysis of national statistics, international reports, and previously completed qualitative studies. The study finds that successful migrant reintegration depends on labor market opportunities, recognition of foreign qualifications, and government support mechanisms. The results of the study also suggest that in Kazakhstan, returnees are mainly employed in self-employment and agriculture, while in South Korea, they are absorbed in high-tech and industrial sectors. Major hurdles for the return migrants are financial limitations, administrative challenges, and socio-cultural issues. The study findings also reveal how different policy approaches create different return experiences in Kazakhstan and South Korea. Kazakhstan's policies aim at stabilizing demography and national identity, while South Korea’s approach is more pragmatic, prioritizing the inclusion of qualified labor. The results also underscore the need for specific reintegration strategies, financial assistance programs, and simplified bureaucratic measures. This study contributes to the scientific public discourse revolving around migration, development and reintegration. The practical significance of the work lies in the possibility of using the obtained data to optimize the return migration strategy and develop effective integration measures that benefit both the returnees and their home countries. By understanding which aspects of migration can successfully accelerate reintegration into society, this study offers recommendations on how countries might improve their public policy regarding this matter.